A Conceptual Model of Islamic Educational Leadership for Managing Constructive Conflict and Strengthening Quality Culture in Madrasahs - Indah Aminatuz Zuhriyah; Siti Aisah; Hidayat Hidayat (Al-Qalam Institue, 2025)
Leadership practices in many educational settings remain largely authoritarian, limiting the effectiveness of constructive conflict management and hindering the development of an inclusive, quality-oriented institutional culture. This study aims to analyze the leadership practices of madrasah principals in conflict management, reconstructing the meaning of the concept of